RESONANT STATES IN A ONE-DIMENSIONAL QUANTUM SYSTEM - Tanimu, A.; Bagudo, I. M. (FUDMA JOURNAL OF SCIENCES, 2020)
In this work, the concept of resonant states (RSs) in a finite square quantum well is presented. We first derive the analytic secular transcendental equations for even and odd states by applying the outgoing wave boundary conditions into the one-dimensional SchrÃ¶dingerâ€™s wave equation. The complex solution of these equations is found using the numerical Newton-Raphson method implemented in MATLAB. We can see in particular, that the RSs present a general class of Eigenstates, which includes bound states, anti-bound states, and normal RSs.